Protective Effects of Lactobacillus plantarum 16 and Paenibacillus polymyxa 10 Against Clostridium perfringens Infection in Broilers - Gong, Li; Wang, Baikui; Zhou, Yuanhao; Tang, Li; Zeng, Zihan; Zhang, Huihua; Li, Weifen (Frontiers in Immunology, 2021)
This study aimed to investigate the protective effects of Lactobacillus plantarum 16 (Lac16) and Paenibacillus polymyxa 10 (BSC10) against Clostridium perfringens (Cp) infection in broilers. A total of 720 one-day-old chicks were randomly divided into four groups. The control and Cp group were only fed a basal diet, while the two treatment groups received basal diets supplemented with Lac16 (1×108 cfu·kg-1) and BSC10 (1×108 cfu·kg-1) for 21 days, respectively. On day 1 and day 14 to 21, birds except those in the control group were challenged with 1×108 cfu C. perfringens type A strain once a day. The results showed that both Lac16 and BSC10 could ameliorate intestinal structure damage caused by C. perfringens infection. C. perfringens infection induced apoptosis by increasing the expression of Bax and p53 and decreasing Bcl-2 expression and inflammation evident by higher levels of IFN-γ, IL-6, IL-1β, iNOS and IL-10 in the ileum mucosa, and NO production in jejunal mucosa, which was reversed by Lac16 and BSC10 treatment except for IL-1β (P < 0.05). Besides, the two probiotics restored the intestinal microbiota imbalance induced by C. perfringens infection, characterized by reduced Firmicutes and Proteobacteria and increased Bacteroidetes at the phyla level, and decreased Bacteroides fragilis and Gallibacterium anatis at the genus level. The two probiotics also reversed metabolic pathways of the microbiota in C. perfringens-infected broilers, including B-vitamin biosynthesis, peptidoglycan biosynthesis, and pyruvate fermentation to acetate and lactate II pathway. In conclusion, Lac16 and BSC10 can effectively protect broilers against C. perfringens infection through improved composition and metabolic pathways of the intestinal microbiota，intestinal structure, inflammation, and anti-apoptosis.